Calcium Level is Lower in Women with Premenstrual Syndrome - Pambudi, Maria F.J. (Indonesian Socety of Obstetrics and Gynecology, 2013)
Objective: To know the relationship of calcium serum levels with the incidence of Premenstrual Syndrome (PMS). Methods: Study subject that fulfil inclusion criteria were asked to fill questionnaires and venous blood sample was taken to measure calcium serum levels. The data is processed and analyzed statistically. Result: The study was conducted on 45 women aged 20-35 years old. Groups of women with PMS found calcium levels between 8.50 to 9.40 mg/dl. Cut off point levels of calcium for PMS incidence was 9.40 mg/dl with 90.9% sensitivity, 75.0% specificity, and accuracy of 86.7%. Conclusion: Women with PMS have lower calcium levels compared to women without PMS. Calcium levels significantly associated with incidence of PMS. [Indones J Obstet Gynecol 2013; 37-2: 99-102] Keywords: premenstrual syndrome (PMS), calcium serum